L-Type Voltage-Gated Calcium Channels Are Required for Extinction, But Not for Acquisition or Expression, of Conditional Fear in Mice - Cain, Chris K. (J Neurosci, 2002)
It has been shown recently that extinction of conditional fear does not depend acutely on NMDA-type glutamate receptors, although other evidence has led to the hypothesis that L-type voltage-gated calcium channels (LVGCCs) play a role in conditional fear. We therefore tested the role of LVGCCs in the acquisition, expression, and extinction of conditional fear of cue and context in mice. Using systemic injections of two LVGCC inhibitors, nifedipine and nimodipine, which both effectively cross the blood–brain barrier, we show that LVGCCs are essential for the extinction, but not for the acquisition or expression, of conditional fear in mice.